Bank Lending and Monetary Policy: Evidence from Deposit Money Banks (DMBs) in Nigeria - Sikiru O, Ashamu (American Finance & Banking Review, 2018)
Monetary policy is aimed at attaining price stability, full employment and moderate long-term interest rates in the economy based on regulatory authority priorities, prevailing economic and financial conditions. Using annualized time series data from DMBs in Nigeria and the Vector Error Correction Model (VECM) as well as the simulates generalized impulse response functions, this study assessed the dynamic interactions between bank lending and monetary policy by observing how banks’ lending patterns are influenced by changes in monetary policy over the years in Nigeria.The result revealed that bank lending responds to short run changes in monetary policy but there is no long run influence from monetary policy to bank loan as banks adjust their portfolio mix in line with the prevailing monetary policy. Similarly, it revealed that changes in monetary policy often create fluctuations on bank health and as such regulatory authority must focus on factors such as monetary policy rate and bank capital that influence bank position in order to attain a significant economic performance using banks as a monetary policy transmission mechanism to the economy.